ADMINISTRATIVE LEADERSHIP (INFORMAL RELATIONSHIPS) AND ITS IMPACT ON EMPLOYEES CASE STUDY (AT LEBANESE PUBLIC SCHOOL) - Dheyauldeen Alaa Abdulameer Al-juboori (Scholars Digest Publishing, 2024)
Business and service organizations are part of the society in which they work. Hence, any organization deals with the human element as the most important element in any organization. Therefore, human relations, especially informal ones, have a major role in how to deal with this element. Therefore, focusing on the existence of these informal relations between the manager and employees will serve the interest of any organization in achieving job satisfaction for its employees, and motivating them to achieve the objectives of the organization. Therefore, in our research, we highlighted the importance of human and informal relations that the manager must enjoy and deal with the members of his organization.